KEWENANGAN YURISDIKSI INTERNATIONAL CRIMINAL COURT TERHADAP PELANGGARAN HAK ASASI MANUSIA - Eza Aulia; Apri Rotin Djusfi; Phoenna Ath Thariq (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2020)
Human rights are a reflection of the development of human civilization, where these rights are things that must be upheld by anyone and anywhere in the world. Therefore, through the Rome Statute a permanent court was formed, namely the International Criminate Court (ICC) which aims to uphold human rights values, especially in relation to gross human rights violations. This research is a normative juridical study that describes the scope of the judicial authority of the ICC as seen by the approach of norms in the Rome Statute. The results illustrate that the ICC has jurisdiction covering jurisdiction over the subject matter, namely genocide, crimes against humanity, war crimes and aggression. Personal jurisdiction includes nationals of state parties, nationals of non-state parties that recognize the Court's jurisdiction and nationals of non-state parties, but cases are brought before the Court based on UN Security Council resolutions.Keyword: Human Right, International Criminal Court